Production of Antioxidant Peptides from Snakehead Fish Using Batch and Continuous Enzymatic Hydrolysis - Kardinan, Selma Aprilla; Yasni, Sedarnawati; Budijanto, Slamet; Kurniadi, Nadine; Sitanggang, S.TP, MSc, Azis Boing (:Agency for Marine and Fisheries Research and Human Resources, Indonesia, 2024)
Bioactive peptides are promising functional ingredients. Due to its high protein content, snakehead fish (Channa striata) extract (SHFE) is one of the suitable parent proteins for bioactive peptides. This study aimed to investigate the production of SHFE-based antioxidative peptides in a conventional batch and continuous system facilitated by an enzymatic membrane reactor (EMR). The effects of different proteases (Alcalase, Neutrase), substrate concentrations, and enzyme-to-substrate ratios were investigated in the batch process. Continuous hydrolysis was then performed under the optimum conditions obtained from the batch process. The optimum conditions based on the antioxidant capacity measured by DPPH and FRAP assays were employing Alcalase with a substrate concentration [S] of 3% (w/v) and an enzyme-to-substrate ratio [E]/[S] of 10% (w/w). Continuous operation was shown to have been performed over a prolonged period, based on the calculated fouling rate. Furthermore, filtration of the resulting permeate with a smaller membrane pore size (2-kDa) increased the antioxidant capacity. This study is expected to increase the production of functional ingredients in snakehead fish.